The persistence of multifocal colonisation by a single ABC genotype of Candida albicans may predict the transition from commensalism to infection - Guilherme Maranhão Chaves; Fernanda Pahim Santos; Arnaldo Lopes Colombo (Memorias do Instituto Oswaldo Cruz, 2012)
Candida albicans is a common member of the human microbiota and may cause invasive disease in susceptible populations. Several risk factors have been proposed for candidaemia acquisition. Previous Candida multifocal colonisation among hospitalised patients may be crucial for the successful establishment of candidaemia. Nevertheless, it is still not clear whether the persistence or replacement of a single clone of C. albicans in multiple anatomical sites of the organism may represent an additional risk for candidaemia acquisition. Therefore, we prospectively evaluated the dynamics of the colonising strains of C. albicans for two groups of seven critically ill patients: group I included patients colonised by C. albicans in multiple sites who did not develop candidaemia and group II included patients who were colonised and who developed candidaemia. ABC and microsatellite genotyping of 51 strains of C. albicans revealed that patients who did not develop candidaemia were multiply colonised by at least two ABC genotypes of C. albicans, whereas candidaemic patients had highly related microsatellites and the same ABC genotype in colonising and bloodstream isolates that were probably present in different body sites before the onset of candidaemia.